যদি \(\cfrac{a}{b+c}=\cfrac{b}{c+a}=\cfrac{c}{a+b}\) এবং \(a+b+c\ne 0\) হয়, তবে প্রমাণ করো যে, \(a=b=c\) Madhyamik 2007


\(\cfrac{a}{b+c}=\cfrac{b}{c+a}=\cfrac{c}{a+b}\)
বা, \(\cfrac{a}{b+c}+1=\cfrac{b}{c+a}+1=\cfrac{c}{a+b}+1\)

[উভয়পক্ষের সঙ্গে 1 যোগ করে পাই]


বা, \(\cfrac{a+b+c}{b+c}=\cfrac{b+c+a}{c+a}=\cfrac{c+a+b}{a+b}\)
বা, \(\cfrac{1}{b+c}=\cfrac{1}{c+a}=\cfrac{1}{a+b}\)

[\(\because a+b+c\ne 0\)]



বা, \(b+c=c+a=a+b\)

[বিপরীত প্রক্রিয়া করে পাই]



\(\therefore b+c=c+a\)
বা, \(b=a\)
আবার, \(c+a=a+b\)
বা, \(c=b\)
\(\therefore a=b=c\) (প্রমাণিত)

Similar Questions